Peran Fasilitator dalam Upaya Meningkatkan Keterampilan Sosial Peserta Didik Sindrom Asperger di Sekolah Alam Saka Kediri - Rahma, Lailatul; Supriyanto, Achmad; Yusuf Sobri, Ahmad (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2023)
Asperger's syndrome is a developmental disorder of social interaction, communication and behavior. Asperger's syndrome is also known as the little professor syndrome because it has a unique behavior, way of thinking and communicating. The existence of obstacles regarding social skills experienced by students with social skills requires that schools have the sensitivity to participate in supporting students' social skills. Social and communication skills are very important for students to be able to show their emotions and feelings appropriately. The research method used in this study is a qualitative research method with data collection techniques of interviews, observation and documentation. This study uses behavioristic theory to find out how the role of the facilitator is in improving students' social abilities by assessing the four main activities, namely: making friends, studying, worshiping and doing activities. The role of the facilitator and the natural school concept promoted by the Sekolah Alam SAKA Kediri contribute to changes in students with Asperger's syndrome..